Working With an Expert Witness: A Lawyer’s Guide - (:unkn) unknown (My University, 2010)
Expert witnesses form an integral part of many legal proceedings where factual evidence must be supplemented with professional opinion. Their services are not inexpensive, and their time should be used appropriately to optimize their effectiveness. It is prudent to select them carefully based upon their fit to the case and their demonstrated skills and experience, and then to prepare them carefully at each stage to ensure that their expert opinions are defensible and not invalidated by inconsistency or poor performance.